Development and optimization of Stationary Electrostatic Bioaerosol Sampler (SEBS) for viable and culturable airborne microorganisms. (May 2022) - Han, Taewon T.; Myers, Nirmala T.; Manibusan, Sydonia; Mainelis, Gediminas
Abstract: This study focused on developing and testing a stationary electrostatic bioaerosol collector with a high concentration rate while preserving viable and culturable microorganisms. Using our earlier advances in the electrostatic collection of airborne microorganisms, we designed and optimized a Stationary Electrostatic Bioaerosol Sampler (SEBS), which incorporates our previously developed wire-to-wire charger and a newly-designed removable particle collector. The sample elution system was also redesigned and optimized to achieve a practical solution yielding a high sample concentration rate. The sampler's collector and its hydrophobic coating methods, collection voltages, and material of sample removal tubes were optimized through an iterative process. SEBS is a two-stage electrostatic sampler with a wire-to-wire charger and a stainless steel collection electrode coated using polydimethylsiloxane (PDMS) coating technique and ultraviolet/ozone surface treatment method. The entire collected sample is eluted into 0.2 or 1 mL of sterile phosphate-buffered saline (PBS) using a customized particle removal system made of glass. The developed SEBS was operated at 20 L/min; its physical and biological performance was compared to the Button filter sampler (SKC, Inc.) when sampling two airborne bacteria and two fungi in the laboratory. On average, SEBS showed actual physical collection efficiency of ∼50% when samples were eluted into 0.2 mL; the efficiency increased to ∼75% when 1 mL elution liquid was used. The average relative viability efficiency reached ∼80%, suggesting that the sampling stress was reduced compared to the filter sampler. The relative culturability efficiency was ∼60%. The use of 0.2 mL elution liquid resulted in a sample concentration rate of ∼5 × 10 4 min -1, which will enable faster detection and determination of viable and culturable bioaerosols, especially when sampling in low concentration environments. Future studies will evaluate SEBS's performance and utility in field studies. Highlights: New sampler is a stand-alone, battery-operated field-deployable bioaerosol sampler. The new sampler has concentration rate of ∼5 × 10 4 min -1 with 0.2 mL elution liquid. SEBS achieved ∼50% collection efficiency with 0.2 mL elution liquid. SEBS exhibited ∼80 viability and ∼60% culturability efficiencies with 1 mL liquid. SEBS is able to determine long-term exposure to bioaerosols at various environments.